MENGEMBANGKAN RESILIENSI AKADEMIK DENGAN MODEL KONSELING JURNALING - Ilham Khairi Siregar; Sefni Rama Putri (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2021)
The education process in higher education allows new students to feel the pressure of changing the learning process from high school to the lecture process in college. Students with considerable pressure feel the condition of academic stress within themselves. Academic stress can be reduced by increasing student academic resilience, namely increasing student endurance in facing difficulties and pressures in the lecture process. This study aims to describe a journaling counseling model to develop student academic resilience in reducing student academic stress. The research method used is library research which is an activity related to the method of collecting library data, reading and recording and processing research materials. Based on the data found, there is a close relationship between journaling counseling in overcoming academic resilience. This is based on the theories found by the author, so further research needs to be done in order to prove the effectiveness of the theory.